Analisi Strategi Pengembangan KSPPS Hanad Quwais Sembada Purwokerto Melalui Pendekatan Analisis Space Matriks - Amalia Kartika; Latifah Nurmaulida Aulia Rahmah; Iqbal Rafly Prasetyo; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the development strategy of the Hanada Quwais Sembada Sharia Savings and Loan Cooperative (KSPPS) Purwokerto Branch. And Sharia Financing Cooperative (KSPPS) Hanada Quwais Sembada Purwokerto Branch through the Strategic Position and Action Evaluation (SPACE) Matrix approach. Strategic Position and Action Evaluation (SPACE) Matrix approach. The method used is qualitative with data collection techniques in the form of interviews and observations. The results analysis shows that KSPPS Hanada Quwais Sembada Purwokerto Branch is located in the aggressive quadrant in the SPACE Matrix, which means that the cooperative has internal strengths and great external opportunities to grow. and great external opportunities to grow. The strategic implications of this position include developing digital-based products and services, diversifying business, strengthening marketing and branding, and establishing partnerships. marketing and branding, and establishing strategic partnerships. With this strategy, it is expected that KSPPS Hanada can streng then its competitive position in the market and increase the number of customers significantly.